2012
DOI: 10.1007/s10856-012-4744-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced early osteogenic differentiation by silicon-substituted hydroxyapatite ceramics fabricated via ultrasonic spray pyrolysis route

Abstract: The influence of silicon-substituted hydroxyapatite (Si-HAp) on osteogenic differentiation was assessed by biological analysis. Si-HAp was prepared by ultrasonic spray pyrolysis (USSP) technique using various amounts of Si (0, 0.8, and 1.6 mass%). Chemical analysis revealed that Si was incorporated into the hydroxyapatite (HAp) lattice with no other crystalline phase and which caused the change of crystal structure. Biological analyses showed that the Si contents affected the cell proliferation and morphology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 30 publications
0
32
0
2
Order By: Relevance
“…Also, the presence of 5 mM and 10 mM Si, induced an up-regulation of BMP2, which plays a role in the maintenance of bone homeostasis and regeneration [43]. A study by Honda et al [44] also demonstrated an increase in OC by osteoblasts cultured on Si substituted HA when compared to HA only. In the same study, an increase in the RUNX2 expression was also observed, which was in contrast to the present study, which may be explained by the difference in cell type used for the study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the presence of 5 mM and 10 mM Si, induced an up-regulation of BMP2, which plays a role in the maintenance of bone homeostasis and regeneration [43]. A study by Honda et al [44] also demonstrated an increase in OC by osteoblasts cultured on Si substituted HA when compared to HA only. In the same study, an increase in the RUNX2 expression was also observed, which was in contrast to the present study, which may be explained by the difference in cell type used for the study.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported [14][15][16], the USSP apparatus was composed of an atomizer, a heating zone (Mullite tube: ID of 2.5 cm and a height of 1 m; electric furnace: ID of 3 cm and a height of 60 cm), a powder collecting zone (test-tube filter), and a controller. The heating section was divided into two electric furnaces: a lower furnace for the evaporation of the solvent from the droplets (temperature: 300 ∘ C) and an upper furnace for the pyrolysis (temperature: 1000 ∘ C).…”
Section: Preparation Of Zn-tcp Powders Using Ussp Technique and Cerammentioning
confidence: 99%
“…In previous works, the preparation of various calcium phosphates, for example, HAp [7,9,10], TCP [11,12], calcium diphosphate [12], calcium metaphosphate [13], trace elements substituted calcium phosphates such as strontiumsubstituted HAp [14], silicon-substituted HAp [15], and silvercontaining HAp [16] by the USSP technique was reported. The effects of the kinds of the starting materials on properties of HAp powders prepared by the USSP technique were also examined [10].…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneously incorporation of multi-walled carbon nanotubes (MWCNTs) and HA nanoparticles in PLLA nanofibers selectively increased adhesion of osteoblast cells and decreased the adhesion of osteoblast competitive cell lines, which was a valuable feature for GBR application [17]. The small trace amount of Mg [46,47], Si [48][49][50], and Zn ions [51,52] integrated in nanofibrous scaffolds have been proved to accelerate cell adhesion and proliferation by delivering the mitogenic stimuli and enhancing channel sensitivity. In addition, chemical signal molecules in the form of growth and differentiation factors [53,54] or plasmid DNA [55,56] incorporated in the nanofibers in a spatially defined manner could achieve corresponding bioactivity in promoting specific differentiation to orchestrate the growth of new tissue.…”
Section: Biological Events Occuring On the Biosis-abiosis Interface: mentioning
confidence: 99%
“…And, their dimension seems to simulate the structure of woven bone, which is the initial bone phenotype formed in the healing procedure after a fracture [49]. The apparent porosity of nanofibers was considered to favor efficient mass transportation of nutrients, oxygen, and waste products [48]. Recent studies have indicated a powerful role of the nanotopographic cues from nanofibers in regulating the osteogenic behavior of stem cells [51,52].…”
Section: Biological Events Occuring On the Biosis-abiosismentioning
confidence: 99%